Extending the vulnerability–stress model of mental disorders: three-dimensional NPSR1 × environment × coping interaction study in anxiety. (November 2020) - Schiele, Miriam A.; Herzog, Katharina; Kollert, Leonie; Schartner, Christoph; Leehr, Elisabeth J.; Böhnlein, Joscha; Repple, Jonathan; Rosenkranz, Karoline; Lonsdorf, Tina B.; Dannlowski, Udo; Zwanzger, Peter; Reif, Andreas; et al.
Abstract : Background: The general understanding of the 'vulnerability–stress model' of mental disorders neglects the modifying impact of resilience-increasing factors such as coping ability. Aims: Probing a conceptual framework integrating both adverse events and coping factors in an extended 'vulnerability–stress–coping model' of mental disorders, the effects of functional neuropeptide S receptor gene ( NPSR1 ) variation (G), early adversity (E) and coping factors (C) on anxiety were addressed in a three-dimensional G × E × C model. Method: In two independent samples of healthy probands (discovery: n = 1403; replication: n = 630), the interaction of NPSR1 rs324981, childhood trauma (Childhood Trauma Questionnaire, CTQ) and general self-efficacy as a measure of coping ability (General Self-Efficacy Scale, GSE) on trait anxiety (State-Trait Anxiety Inventory) was investigated via hierarchical multiple regression analyses. Results: In both samples, trait anxiety differed as a function of NPSR1 genotype, CTQ and GSE score (discovery: β = 0.129, P = 3.938 × 10 −8 ; replication: β = 0.102, P = 0.020). In A allele carriers, the relationship between childhood trauma and anxiety was moderated by general self-efficacy: higher self-efficacy and childhood trauma resulted in low anxiety scores, and lower self-efficacy and childhood trauma in higher anxiety levels. In turn, TT homozygotes displayed increased anxiety as a function of childhood adversity unaffected by general self-efficacy. Conclusions: Functional NPSR1 variation and childhood trauma are suggested as prime moderators in the vulnerability–stress model of anxiety, further modified by the protective effect of self-efficacy. This G × E × C approach – introducing coping as an additional dimension further shaping a G × E risk constellation, thus suggesting a three-dimensional 'vulnerability–stress–coping model' of mental disorders – might inform targeted preventive or therapeutic interventions strengthening coping ability to promote resilient functioning.